Gradients of physical and biochemical cues on polyelectrolyte multilayer films generated via microfluidics - Almodóvar, Jorge (2013)
The cell microenvironment is a complex and anisotropic matrix composed of a number of physical and biochemical cues that control cellular processes. A current challenge in biomaterials is the engineering of biomimetic materials which present spatially controlled physical and biochemical cues. The layer-by-layer assembly of polyelectrolyte multilayers (PEM) has been demonstrated to be a promising candidate for a biomaterial mimicking the native extracellular matrix. In this work, gradients of biochemical and physical cues were generated on PEM films composed of hyaluronan (HA) and poly(l-lysine) (PLL) using a microfluidic device. As a proof of concept, four different types of surface concentration gradients adsorbed onto the films were generated. These included surface concentration gradients of fluorescent PLL, fluorescent microbeads, a cross-linker, and one consisting of a polyelectrolyte grafted with a cell adhesive peptide. In all cases, reproducible centimeter-long linear gradients were obtained. Fluorescence microscopy, Fourier transform infrared spectroscopy and atomic force microscopy were used to characterize these gradients. Cell responses to the stiffness gradient and to the peptide gradient were studied. Pre-osteoblastic cells were found to adhere and spread more along the stiffness gradient, which varied linearly from 200 kPa–600 kPa. Myoblast cell spreading also increased throughout the length of the increasing RGD-peptide gradient. This work demonstrates a simple method to modify PEM films with concentration gradients of non-covalently bound biomolecules and with gradients in stiffness. These results highlight the potential of this technique to efficiently and quickly determine the optimal biochemical and mechanical cues necessary for specific cellular processes.